2021
DOI: 10.3390/molecules26051347
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Bioactive Characterisation of Impatiens walleriana

Abstract: The attractive colour characteristics of the flowers of the species Impatiens walleriana have been arousing great interest in the food industry, which is looking for potential natural sources of colouring ingredients. In this sense, the present work focused on the chemical and bioactive characterization of pink and orange flowers of I. walleriana. The phenolic compounds were determined by HPLC-DAD-ESI/MS; in addition, different bioactivities (antioxidant, antimicrobial, anti-inflammatory and cytotoxicity) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 41 publications
(50 reference statements)
2
3
0
1
Order By: Relevance
“…Reports on the colourimetry of Impatiens flowers are scarce. However [30], when observing petals of the species Impatiens walleriana L., the orange petals presented L* and b* values higher than those presented by the pink variety, translating to light and yellowish, while the pink petals presented higher values in the a* parameter, suggesting a more intense tone in the red range, a fact that corresponded to the information also obtained by this work.…”
Section: Evaluation Of Colour Parameterssupporting
confidence: 85%
See 1 more Smart Citation
“…Reports on the colourimetry of Impatiens flowers are scarce. However [30], when observing petals of the species Impatiens walleriana L., the orange petals presented L* and b* values higher than those presented by the pink variety, translating to light and yellowish, while the pink petals presented higher values in the a* parameter, suggesting a more intense tone in the red range, a fact that corresponded to the information also obtained by this work.…”
Section: Evaluation Of Colour Parameterssupporting
confidence: 85%
“…The most promising IC 50 values were, respectively, 2.46 µg/mL (LOX), 18.4 µg/mL (COX-1) and 1.9 µg/mL (COX-2) for the nanofiltration fraction (NF), which can be used for inflammatory diseases. Pires Junior et al [30] in turn observed the anti-inflammatory activity of hydroethanolic extract (80:20, v/v) of pink and orange flowers of the species I. walleriana, in which diagnosed values were 312.1 ± 5.5 µg/mL for the orange extract and 349.21 ± 12.8 µg/mL for the pink extract. It can be observed that the extracts BP and BO present more promising values when compared to the similar study made with the extract of flowers of the species I. walleriana.…”
Section: Bioactivities Evaluationmentioning
confidence: 97%
“…L., as promising natural colorants with high potential for industrial application. The same suggestion was made by Pires et al [78], who highlighted the anthocyanin extracts from Impatiens walleriana flowers as a promising colorant of orange and pink shades.…”
Section: Anthocyaninssupporting
confidence: 67%
“…[78] Pelargonidin-O-hexosídeo-O-desoxihexoside-hexoside [78] Malvidin-3-O-glucoside Robinia hispida L.…”
Section: Pelargonidin-o-p-coumaroil-hexoside-o-acetyl-hexosidementioning
confidence: 99%
“…En un estudio realizado por Pires et al (2021) se identificaron y cuantificaron compuestos fenólicos no antociánicos y antocianínicos en flores rosas y naranjas de I. walleriana. Con respecto a los compuestos no antociánicos, se identificaron cuatro ácidos fenólicos (derivados de ácido cafeico y pcumárico) y en cuanto a los antocianínicos: cuatro derivados de pelargonidina, tres derivados de malvidina y tres derivados de peonidina.…”
Section: Fitomejoramiento: Coloración De Las Floresunclassified